Mengidolakan Artis Non Muslim Menurut Pandangan Hukum Islam - A Riyanda Rizky; Ahmad Sanusi Luqman; Kamaliah Kamaliah (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The phenomenon of idolizing non-Muslim artists, particularly within the global popular culture, has increasingly spread among Muslim communities. This study aims to analyze the practice of idolizing non-Muslim artists from the perspective of Islamic law, considering the principles of faith (aqidah), morality (akhlaq), and sharia. The research employs a qualitative approach with literature analysis, encompassing studies of Quranic verses, hadith, and the opinions of Islamic scholars. The findings indicate that idolizing non-Muslim artists can be acceptable in Islam as long as it does not contradict the fundamental principles of the religion, such as preserving faith, avoiding behavior contrary to sharia, and not neglecting religious obligations. However, if such idolization involves excessive admiration (ghuluw), imitation of behaviors that violate Islamic law, or negative influences on one’s faith, it is considered impermissible. This study is expected to provide a deeper understanding of the boundaries in idolizing public figures who are non-Muslims and to serve as guidance for Muslims in maintaining their religious identity in an era of cultural globalization.